2002
DOI: 10.1295/polymj.34.868
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell Type Polystyrene Latex Possessing Reactive Poly(ethylene glycol) Brushes on the Surface for High Performance Immunodiagnostics

Abstract: ABSTRACT:Amphiphilic poly(ethylene glycol)-b-polylactide (PEG/PLA) block macromonomers with an aldehyde group at the PEG chain end and a methacryloyl group at the PLA chain end were quantitatively synthesized by anionic polymerization. PEGylated latex particles were then prepared by dispersion radical copolymerization of the PEG/PLA block macromonomer with styrene in water. PEG/PLA macromonomer itself works as a surfactant to stabilize styrene droplets in the copolymerization process. Acetal groups at the PEG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Synthetic route to a stimuli-responsive PEGylate nanogel. ously that the average surface area occupied by each PEG molecule is not influenced by the size of the particle obtained by the dispersion polymerization in the presence of PEG macromonomers with the same molecular weight [47]. However, Wu et al [48] have reported that the density of the tethered PEG chain decreases with increasing molecular weight, which eventually influences the n-potentials of the nanogels because the carboxyl group locates adjacent to the end of PEG tethered chain.…”
Section: Synthesis Of Heterobifunctional Peg Macromonomer [39]mentioning
confidence: 99%
“…Synthetic route to a stimuli-responsive PEGylate nanogel. ously that the average surface area occupied by each PEG molecule is not influenced by the size of the particle obtained by the dispersion polymerization in the presence of PEG macromonomers with the same molecular weight [47]. However, Wu et al [48] have reported that the density of the tethered PEG chain decreases with increasing molecular weight, which eventually influences the n-potentials of the nanogels because the carboxyl group locates adjacent to the end of PEG tethered chain.…”
Section: Synthesis Of Heterobifunctional Peg Macromonomer [39]mentioning
confidence: 99%
“…Tailor made charged surfaces can be tuned for the selective adsorption of the protein of interest and so separate it from a biological system based on its surface charge, specific area and hydrophobicity. Various types of coating with different functional groups [1][2][3] and polymers 4,5 have been used to control (enhance/reduce) protein adsorption on different solid surfaces. The adsorption of proteins on modified surfaces is mostly influenced by charged molecules.…”
Section: Introductionmentioning
confidence: 99%
“…To introduce a functionality on the surface of the core-shell nanosphere, we have employed a heterotelechelic PEG, which possessed an acetal group at one end and a methacryloyl group at the other end, for the dispersion polymerization. 15 Thus, the biotin-installed core-shell type nanosphere was prepared.…”
Section: Introductionmentioning
confidence: 99%